2012
DOI: 10.5455/aim.2012.20.196-197
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Renal Vessels

Abstract: Knowledge of the variations of the renal artery has grown in importance with increasing of renal transplants, vascular reconstructions and various surgical and radiologic techniques performing in recent years. We report the presence of unilateral doubled renal vessels, discovered on routine dissection of a male cadaver, on the right side; additional renal artery originated from the abdominal aorta. In addition the right suprarenal gland received arteries from right renal and inferior phrenic arteries only. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Natsis et al [ 41 ] reported no statistically significant relationship ( p > 0.05) between gender and the side on which the supernumerary renal artery was situated. However, several authors have observed a higher incidence in males than females [ 3 , 61 , 64 , 82 , 83 ], whereas others conclude the opposite [ 56 , 66 , 84 , 85 ] ( Table IV ).…”
Section: Morphological and Demographic Aspectsmentioning
confidence: 99%
“…Natsis et al [ 41 ] reported no statistically significant relationship ( p > 0.05) between gender and the side on which the supernumerary renal artery was situated. However, several authors have observed a higher incidence in males than females [ 3 , 61 , 64 , 82 , 83 ], whereas others conclude the opposite [ 56 , 66 , 84 , 85 ] ( Table IV ).…”
Section: Morphological and Demographic Aspectsmentioning
confidence: 99%
“…[8] ( fig.1,2,3) Knowledge of the variations of the renal artery has grown in importance with increasing numbers of renal transplants, nephrectomies, segmental resection and various surgical and radiologic techniques being performed in recent years. [9] Transplanting a kidney with accessory renal arteries has several theoretical disadvantages like acute tubular necrosis and rejection episodes and decreased graft functioning [4] . Knowledge of supernumerary renal arteries is essential before performing any transplantation surgeries since microvascular techniques can be employed to reconstruct the renal arteries during end to end anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…The right renal artery is longer and often higher than the left. Although a single renal artery supplying each kidney is classically described, it is subject to anatomical variations frequently 2 . Knowledge of these anatomical variations of the renal vasculature is of great importance with the advent of vascular reconstructive surgeries, renal transplants, and various radiological and urological procedures carried out in this region 2 .…”
Section: Introductionmentioning
confidence: 99%